MENINGKATKAN KEMAMPUAN LITERASI NUMERASI DAN BERNALAR KRITIS MENGGUNAKAN MODEL TEO STAY TO STRAY (TSTS) BERBANTUAN MEDIA FLASHCARD MATEMATIKA PADA SISWA KELAS V SD NEGERI 067241 MEDAN DENAI TAHUN PEMBELAJARAN 2024/2025 - Asima Indra Sihotang; M. Fauzi Hasibuan; Lasma Silaban (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research addresses the low numeracy literacy, critical thinking skills, and academic performance of fifth-grade students at SD Negeri 067241 Medan Denai. To tackle these issues, the author implemented the Two Stay Two Stray (TSTS) learning model assisted by flashcard media with the goal of improving numeracy literacy, critical thinking skills, and mathematics learning outcomes. This classroom action research involved fifth-grade students at SD Negeri 067241 Medan Denai as subjects. The results showed an improvement in numeracy literacy, critical thinking skills, and student learning outcomes in mathematics, specifically in the area of surface area of plane figures, after improvements were made in the second cycle. Initially, only 7 students (26%) achieved mastery with an average score of 47.81. After the first cycle, the number of students who achieved mastery increased to 12 (44%) with an average score of 70. In the second cycle, 23 students (85%) reached mastery with an average score of 90. The intervention was discontinued after the second cycle as the success criteria had been met. The study concludes that the use of the Two Stay Two Stray (TSTS) learning model assisted by flashcard media successfully improved numeracy literacy, critical thinking skills, and mathematics learning outcomes for fifth-grade students at SD Negeri 067241 Medan Denai.